Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00103-012-1503-6
|View full text |Cite
|
Sign up to set email alerts
|

Die DONALD Kohorte

Abstract: The DONALD study has been conducted in Dortmund, Germany since 1985 to examine the complex relations between nutritional intake, metabolism and growth from infancy to adulthood. Every year, approximately 40 infants are newly recruited into the open cohort study. Examinations conducted at ages 3, 6, 9, 12, 18, 24 months and then annually until young adulthood, comprise anthropometry, a 3 day weighed dietary record, a 24 h urine sample (from age 3-4 years onwards), medical examinations and parental interviews. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 45 publications
(29 reference statements)
1
15
0
1
Order By: Relevance
“…The Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study is a longitudinal open cohort study [28], [29]. Since 1985, about 35-40 newborns are annually recruited into the study examined at ages 3, 6, 9, 12 and 18 months and annually thereafter until young adulthood [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study is a longitudinal open cohort study [28], [29]. Since 1985, about 35-40 newborns are annually recruited into the study examined at ages 3, 6, 9, 12 and 18 months and annually thereafter until young adulthood [28].…”
Section: Methodsmentioning
confidence: 99%
“…Since 1985, about 35-40 newborns are annually recruited into the study examined at ages 3, 6, 9, 12 and 18 months and annually thereafter until young adulthood [28]. The elaborate design of the DONALD Study results in an over-representation of children from families with high socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
“…Fourthly, the participants of the DONALD Study are characterized by a high socio-economic status as compared to the German population, which may however have reduced our vulnerability to residual confounding. It is further worthwhile mentioning that a nationwide German study on breastfeeding conducted 1997-1998 found comparable numbers with respect to prevalence and duration of breastfeeding [22] .…”
Section: Discussionmentioning
confidence: 84%
“…The DONALD Study is an ongoing, open cohort study conducted in Dortmund, Germany. Details on this study have been described elsewhere [22] , [23] . Every year, an average of 35-40 infants are newly recruited and first examined at the age of 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Bei der Gestaltung der Speisepläne dienten Verzehrdaten aus der DONALD-Studie [12] als Orientierung. Hierfür wurden aus vorliegenden 3-Tage-Wiege-Ernährungsprotokollen aus den Jahren 2007 -2014 für 3 Altersgruppen (4 -6 Jahre, 10 -12 Jahre, 15 -18 Jahre) jeweils diejenigen 10 Protokolle mit der höchsten Ernährungsqualität, gemessen an einem Nährstoffqualitätsindex [13], ausgewählt.…”
Section: Der Speiseplanunclassified